Evaluation of how a curriculum change in nurse education was managed through the application of a business change management model: A qualitative case study. (January 2016) - Chowthi-Williams, Annette; Curzio, Joan; Lerman, Stephen
Summary: Background: Curriculum changes are a regular feature of nurse education, yet little is known about how such changes are managed. Research in this arena is yet to emerge. Objective: Evaluation of how a curriculum change in nurse education was managed through the application of a business change management model. Method: A qualitative case study: the single case was the new curriculum, the Primary Care Pathway. Participants and Setting: One executive, three senior managers, two academics and nineteen students participated in this study in one faculty of health and social care in a higher education institution. Results: The findings suggest that leadership was pivotal to the inception of the programme and guiding teams managed the change and did not take on a leadership role. The vision for the change and efforts to communicate it did not reach the frontline. Whilst empowerment was high amongst stakeholders and students, academics felt dis-empowered. Short-term wins were not significant in keeping up the momentum of change. The credibility of the change was under challenge and the concept of the new programme was not yet embedded in academia. Conclusion: Differences between the strategic and operational part of the organisation surfaced with many challenges occurring at the implementation stage. The business change model used was valuable, but was found to not be applicable during curriculum changes in nurse education. A new change model emerged, and a tool was developed alongside to aid future curriculum changes. Highlights: Curriculum changes in nurse education were evaluated retrospectively though using a business change model. There was division between the strategic and operational parts of the organisation. Most challenges were found at the implementation stage. A new change management model for managing future curriculum changes was created. A tool to use alongside the change management model was developed.